The effect of astaxanthin on resistance of juvenile prawns Macrobrachium nipponense (Decapoda: Palaemonidae) to physical and chemical stress - Tizkar, Babak; Seidavi, Alireza; Ponce-Palafox, Jesús Trinidad; Pourashoori, Parastoo (Revista de Biología Tropical, 2014)
In recent years, the use of new scientific techniques has effectively improved aquaculture production processes. Astaxanthin has various properties in aquaculture and its antioxidant benefits have been closely related to stress resistance; besides, it is an essential factor for growth in many crustaceans and fish. The objective of this study was to evaluate the resistance of prawn (Macrobrachium nipponense) fed diets containing different amounts of astaxanthin (AX) to the shock and stress of different physicochemical environments. A 70-day trial was conducted to evaluate the effect of supplementation of a source of astaxanthin (Carophyll Pink, 10% astaxanthin, w/w, Hoffman-La Roche, Switzerland) at various levels in the diet of M. nipponense juveniles. Four dry diets were prepared: AX0 without astaxanthin, AX50 with 50mg/kg, AX100 with 100mg/kg, and AX150 with 150mg/kg astaxanthin. The feeding trial was conducted in a recirculation water system consisting of 12 fiberglass tanks (1 000L) used for holding prawns. Three replicate aquaria were initially stocked with 36org/m2 per tank. During the trial, prawns were maintained on a 12:12-h light:dark photoperiod with an ordinary incandescent lamp, and the water quality parameters were maintained as follows: water temperature, 25-26°C; salinity, 1g/L; pH, 8.5-8.8; dissolved oxygen, 6.0-6.5mg/L; and ammonia-nitrogen, 0.05mg/L. Incorporation of AX, production output, and physiological condition were recorded after 10 weeks of feeding. At the end of the growing period, the prawns were exposed to thermal shock (0°C), ammonia (0.75mg/L), and reduced oxygen (0.5mg/L). The time to lethargy and the time to complete death of the prawns were recorded. The results showed that control prawns had the shortest time to lethargy and death compared with prawns subjected to the other treatments. The results of this study have shown that the amount of muscle tissue and gill carotenoids in prawn fed with an AX150 diet showed greater reduction than those exposed to other treatments. It is possible that higher levels of astaxanthin in the body under oxygen reduction stress can be beneficial for prawns. These results suggest that male prawns showed lethargy earlier than females, and the percentage of carotenoid reduction in muscle and gill tissues was higher in males.